Parole Release and Recidivism Risk Factors - Petrović, Vera; Jovanić, Goran (Zbornik Instituta za kriminološka i sociološka istraživanja, 2017)
Since their introduction in the Republic of Serbia to this day, by the amendments to the legislative materials, the formal postulates concerning parole release have been altered a number of times. This paper depicts the changes in legal provisions on parole release in Serbia and the solutions in foreign systems, as well as the examples of good practice which are considered to be adequate for incorporation into our legislation. The subjects of the research are court decisions on parole release and consideration of recidivism risk factors. The goal is the determination of the different kinds and volumes of scientifically and empirically proven factors that competent courts take into consideration when they release on parole. The research was done on a sample of 121 files of convicts serving their sentences in Užice County Jail and Padinska Skela Correction Facility. The research results indicate that in the course of parole release, the facts, which have been determined to represent recidivism risk factors, are only partly taken into account.